The Advantage of Being Less Protected: Children’s Spatial Orientation in the City of Jakarta - Ajisuksmo, Clara R. P.; Baskara, Agustina H; Neidhardt, Eva (Makara Human Behavior Studies in Asia, 2018)
Path integration as a central process in spatial orientation is a basic cognitive competence used to update spatial positioning while walking. Children develop this competence via self-directed path-finding experiences. This study examines the spatial orientation competences of pre-school children in inner-city Jakarta. The influence of parental protectiveness on path integration competence was investigated, and the children’s spatial ability was measured using paper-and-pencil tests. Thirty pre-school children from poor families in three different sub-districts of inner-city Jakarta (Jatinegara Cipinang, Besar Selatan, and Bukit Duri) were tested. Results showed that children who were used to roaming more freely performed better in spatial orientation than those whose parents granted them less freedom to wander alone. Small significant correlations between spatial ability tests and path integration competence were observed. However, being able to move freely in everyday life was far more important than spatial ability measured by pen-and-paper tests.